1999
DOI: 10.1111/jnc.1999.72.1.318
|View full text |Cite
|
Sign up to set email alerts
|

Picrotoxin Blockade of Invertebrate Glutamate‐Gated Chloride Channels: Subunit Dependence and Evidence for Binding Within the Pore

Abstract: Glutamate-gated chloride channels have been described in nematodes, insects, crustaceans, and mollusks. Subunits from the nematode and insect channels have been cloned and are phylogenetically related to the GABA and glycine ligand-gated chloride channels. Ligand-gated chloride channels are blocked with variable potency by the nonselective blocker picrotoxin. The first two subunits of the glutamate-gated chloride channel family, GluClalpha and GluClbeta, were cloned from the free living nematode Caenorhabditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 43 publications
1
68
2
Order By: Relevance
“…Picrotoxin Can Access Its Site in the S15ЈQ Mutant in the Absence of Channel Opening-The ability of picrotoxin to access its site is poor in the absence of the agonist in GABA A and glutamate-gated Cl Ϫ channels (3,5). However, picrotoxin can efficiently access its site without channel opening in glycine ␣1 receptors (13); we confirmed this finding in the present investigation (data not shown).…”
Section: Figsupporting
confidence: 82%
See 4 more Smart Citations
“…Picrotoxin Can Access Its Site in the S15ЈQ Mutant in the Absence of Channel Opening-The ability of picrotoxin to access its site is poor in the absence of the agonist in GABA A and glutamate-gated Cl Ϫ channels (3,5). However, picrotoxin can efficiently access its site without channel opening in glycine ␣1 receptors (13); we confirmed this finding in the present investigation (data not shown).…”
Section: Figsupporting
confidence: 82%
“…However, single channel analysis has shown that picrotoxin lacks the flickery effect that is typical of a classical channel blocker (12). In addition, picrotoxin inhibition is voltage-independent in these channels (3,12,13). Furthermore, other reports have demonstrated little or no usefacilitated block by picrotoxin in glycine and GABA C receptors, respectively (13,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations